MEMBANGUN BRAND AWARENESS, BRAND IMAGE, BRAND ATTITUDE DAN BRAND LOYALTY KUKU BIMA ENERGI MELALUI KOMUNIKASI IKLAN TELEVISI - , Tiyas Susilaningrum Hamumpuni, Dr. Ike Janita Dewi, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this research is to evaluate the effect of brand awareness, brand image, brand attitude, and brand loyalty of Kuku Bima Energi through television advertisement communication. The writer conducted this research by disseminating questionnaires to 200 respondents of Kuku Bima Energi target market, i.e. respondents in the segment of C, D, and E. The result showed that Kuku Bima Energi advertisements were able to build Brand Awareness to users and non-users. The level of awareness among this energy drink users was high, while the non-users were considered as having sufficient awareness since the awareness was still above the average. In addition, there was a significant brand awareness effect to brand image, brand image to brand attitude, and brand attitude to brand loyalty of Kuku Bima Energi. There was also a significant difference between the Kuku Bima Energy users and nonusers in the establishment of brand awareness, brand image, and brand attitude.